Case Report: Pulmonary and gastrointestinal involvement in a rare case of Waldenström’s Macroglobulinemia in French Guiana - Aissaoui, Houari; Gaudard, Dana; Hadj Amara, Ghazi; Aboikoni, Alolia; Lingibe, Yanna; Louvel, Dominique (Frontiers in Medicine, 2025)
BackgroundWaldenström’s Macroglobulinemia (WM) is a rare lymphoproliferative disorder characterized by the proliferation of lymphoplasmacytic cells producing monoclonal immunoglobulin M (IgM). Extra-hematopoietic involvement, although rare, can affect the gastrointestinal tract in approximately 4% of cases and the lungs in 3–5% of cases. This case highlights the diversity of extramedullary manifestations in WM and underscores the importance of performing pulmonary and gastrointestinal endoscopies with systematic biopsies for optimal disease management.Case presentationWe report the case of a 60-year-old Haitian man diagnosed with WM in January 2023 following an episode of acute respiratory failure. Biopsies revealed lymphoplasmacytic infiltration in both the bronchial and gastrointestinal mucosa. Biopsies revealed lymphoplasmacytic infiltration in both the bronchial and gastrointestinal mucosa, despite normal macroscopic findings during gastrointestinal endoscopy.ConclusionThis case emphasizes the importance of systematic biopsies during endoscopic examinations, even in the absence of visible lesions, to detect lymphoplasmacytic infiltration in WM. These findings could help in changing the approach to disease management and improving patient outcomes.